Comparative Stress–Strain Study of Rubber and Metal: Implications for Cutting Resistance - Hagai, Rafael (Jurnal Sains dan Teknologi (JSIT), 2025)
This study aims to investigate the physical phenomenon that occurs when a sharp knife is inserted into rubber material under various strain conditions. The analysis is based on experimental data from "Nuttras," examining four distinct strain values: ε = 0.5, ε = 5.333, ε = -1 (compressive strain), and an extremely small tensile strain (ε = 1.67×10⁻⁹). The findings reveal a fundamental difference between the hyperelastic, non-linear behavior of rubber and the linear, brittle nature of metal. The force required for cutting ranged from 1.67 μN to 5333 N. The results demonstrate that the non-linear elasticity of rubber, which allows for significant energy absorption and chain realignment, prevents the knife from causing instant fracture. This highlights a key mechanical property distinction with significant implications for material design and application.